The potential of various seeds as angiotensin-I converting enzyme inhibitory peptides derived from protein hydrolysate: a short review. Issue 1 (April 2021) - Priyanto, A D; Putranto, A W; Hsu, J L
Abstract: Angiotensin-I converting enzyme (ACE) plays an imperative role in the blood pressure system. It generates intense vasoconstriction by converting angiotensin-I to angiotensin-II. Counter regulation of ACE may reduce blood pressure. One of the most frequently used medications for treating hypertension cases to inhibit ACE activity is a commercial synthetic drug. However, long-term consumption of those drugs could lead to suffering dangerous and unpredictable side effects. There have been many studies recently concerning the bioactive peptides as ACE inhibitors derived from various seeds. It has been reported that non-thermal extraction methods were used to obtain the protein from inside the cell. However, there was a lack of information focusing on ACE inhibitory peptides from plant biomass. Therefore, this review aimed to summarise and gather the point of view of the plant-derived ACE inhibitory peptides from raw material sources, processing, and peptide sequences studies. This paper contributed to explaining a comprehensive review of ACE inhibitory peptides from edible materials and proposes a fascinating discussion due to the sources being discovered derived from edible protein and safer grade. Various seeds in Indonesia may have future potential for ACE inhibitory peptides as natural therapeutic agents.